Effect of injectable trace mineral supplement and vitamins A and E on production and milk composition of Holstein cows - Collet, Silvana Giacomini; Demeda, Mateus Alan; Taffarel, Gustavo Vinícius; Taffarel, Letícia; Girardini, Lilian Kolling; Nesi, Cristiano Nunes; Hoff, Marlon Celso; Leal, Marta Lizandra do Rego (Revista de Ciências Agroveterinárias, 2018)
The purpose of this research was to evaluate the use of mineral traces (Copper, Zinc, Selenium, and Manganese), as well as vitamins A and E in injectable forms on the production and composition of Dutch cow milk at the end of the transitional period, until after 60 days of lactation. 31 females were divided into two experimental groups: the treated grou p (n= 15) that received mineral supplements (10 mg of Copper, 40 mg of Zinc, 5 mg of Selenium, and 10 mg of Manganese) and vitamins (175 mg of vitamin A and 250 mg of vitamin E) and injections (5 mL minerals trace solution and 5 mL vitamin solution subcutaneously). After 225 gestation days, 255 pregnancy days and the estimated day of delivery, the control group (n = 16) that received injections of the sterilizing solution (5 mL dosage from a subcutaneous via) on the same days as the treated group. Milk samples were collected on the 7th, 14th and 21st days after birth, which were used to evaluate the production, the quality (colostrum), and composition (fat, lactose, protein, nonfat dry extract, total solids, urea, and somatic cell count (SCC)). The initial and minimum values estimated by the model indicated that there was not a difference in milk production and SCC levels between the groups. Among the remaining milk components, only the urea showed significant differences between treated and untreated groups (p= 0.002). Also, there were no significant differences observed in the quality of the colostrum. This leads us to believe that the use of injectable solutions containing Cu, Zn, Se, Mn and vitamins A and E have no effect on the composition of urea in the milk, and also showed no effect on SCC and other milk components, as well as in production. However, more studies should be performed.